Development and Engineering Properties of Construction Materials Made Using Melted Plastics Wastes as the Only Binding Phase - Thiam, Moussa (Université d'Ottawa / University of Ottawa, 2021)
Modernization has brought about steady increase in the consumption of goods and services by human societies across the globe, which mostly driven by both population growth and the change of individual living standards. This, of course, leads to an ever-increasing waste production that ends up in landfills and very often as a source of pollution on natural ecosystems, especially in the low and middle-income countries where waste management is almost inexistent. The management of waste streams is a huge challenge for developed countries as well, where societal and environmental impacts are visible despite massive investments in waste management. One of the most problematic waste materials is plastic, which can remain in nature for over 100 years without degradation, leading to serious environmental concerns. As one of the most significant innovations of the 20th century, plastic is a widely used and cost-effective material for many applications. After their useful lifetimes, their management is problematic. Thus, robust and innovative approaches of managing such waste material are needed in order to mitigate the problem. One of the innovative approaches of tackling the menace cause by plastic waste is through its incorporation into the construction materials. This thesis seeks to address this problem by exploring the use of melted plastic wastes (High Density Poly Ethylene, HDPE and Low Density Poly Ethylene, LDPE) as binder in developing new construction materials (mortar with melted plastic as the only binder, MPB and Plastic Waste Crete, PWC) as an alternative to partially replace traditional concrete and mortar, or finding other engineering uses for this type of waste. Worldwide, about 190 m3 of concrete is poured every second, which translates to 6 billion m3 per year and making it, one of the most widely used manufactured materials. However, the production of concrete requires water and cement. Cement is expensive, and its production contributes to the emission of environmentally polluting gases. Replacing this binding element with recycled plastic derivatives would have significant economic and environmental benefits. In addition to the elimination of cement cost, this will result in water savings, which is especially important for areas without fresh water scarcity. Some researchers have used plastics in concrete and mortars as additives and/or replacement for fine and coarse aggregates. In addition, different types of plastics have been used in bitumen as an additive to reduce construction cost and improve sustainability by adding value to wastes materials. However, there is paucity of technical information about the use of the melted HDPE and LDPE plastic wastes as the only binding phase in concrete- or mortar-like materials. Moreover, many parameters such as preparation conditions, field variables, constituent elements, and final applications have impacts on the performance of construction materials Thus, the key objective of this PhD research is to develop the mortar with plastic binder (MPB) and PlasticWasteCrete (PWC) by using molten HDPE and LDPE plastic wastes as the only binder as well as to investigate the engineering properties of these new types of construction materials. The plastic contents of 45%, 50%, 60% and 65% and HDPE to LDPE ratios of 40/60, 50/50, and 60/40 were selected for the experimental tests. Clean river sand was used as the only aggregate for the MPB, while both sand and gravel were used for the PWC. Various tests were then performed on prepared MPB and PWC samples at different curing times from early to advanced ages to assess their engineering properties. These tests were conducted in accordance with the ASTM standards to evaluate the mechanical properties (compressive strength and splitting tensile strength), permeability and density of the MPB and PWC materials. Additional tests were carried out to analyze the products at the microstructural level (optical microscope, SEM, MIP and thermogravimetric analysis) to gain an insight into the microstructural properties of the developed materials and how that affect their engineering properties. The compressive strength tests revealed the optimal plastic content for the MPB and PWC with the best strength performance. The average compressive strength values for various optimal formulations after 28 days were found to be in the range of 9 to 18 MPa. The splitting tensile strength for the new materials from 1 to 28 days of curing time, were found to be between 1 and 5 MPa. The average hardened density of the MPB and PWC is about 2 g/cm3, which makes them lightweight material according to RILEM classification. In addition, various absorption tests (capillary and immersion) were performed on different MPB and PWC samples, and the obtained results showed that they are porous materials having lower rate of absorption than the traditional cementitious materials (mortar, concrete). This observation was supported by the results from both MIP and SEM analyses. Finally, thermogravimetric analysis provided interesting details on the thermal decomposition of the new materials, with significant changes or mass loss for these products being observed only at temperatures higher than 300°C. The findings from this study suggest MPB and PWC made with melted plastic waste as the only binder have a promising potentials for use in construction. The research conducted in this PhD study offers a good understanding of the engineering properties of the materials as well as the optimal formulations that yield best performance in terms of strength and durability. In summary, it provides useful technical information and tools on the MPB and PWC that will contribute in setting guidelines on the optimal applications of these products in the field of construction in order to have safe, durable and cost-effective structures. Résumé Avec la modernisation de nos sociétés, les habitudes ont considérablement changé, ainsi, on observe une forte consommation des biens et services, due à l’augmentation de la population et l’amélioration de leurs conditions de vie. Ce qui conduit à une augmentation considérable des quantités des déchets qui terminent leurs cycles au niveau des décharges ou dans les océans/fleuves devenant ainsi une source de source de pollution des écosystèmes naturels, surtout dans les pays à revenu faible et intermédiaire avec des systèmes défaillants ou moins performants de gestion des déchets. La gestion des flux de déchets est aussi un défi pour certains pays développés, où les impacts sociaux et environnementaux sont visibles en dépit des investissements massifs dans ce secteur. Parmi ces déchets, nous avons les plastiques, l’une des innovations du 20e siècle avec des qualités versatiles et coût faible, se trouve partout dans nos vies quotidiennes. Après leur utilisation, les plastiques deviennent des déchets qui peuvent rester dans la nature plus de 100 ans sans aucune dégradation, avec des conséquences néfastes sur l’Homme et l’environnement. Ainsi, une approche robuste et innovante de gestion de ces déchets est nécessaire afin d'atténuer leurs impacts. L'une des approches innovantes pour réduire l’impact causé par les déchets plastiques consiste à les incorporer dans les matériaux de construction. Ainsi, le problème est abordé dans cette thèse en développant des technologies permettant de recycler les plastiques fondus comme liant dans les nouveaux matériaux de construction (MPB et PWC), afin d’offrir une alternative pour remplacer partiellement le béton / mortier traditionnel. Le béton est l’un des matériaux les plus utilisés au monde, avec environ 190 m3 coulés chaque seconde, correspondant à 6 milliards de m3 par an. Cependant, la production de béton nécessite de l'eau et du ciment. Le ciment coûte cher et sa production contribue à l'émission de gaz polluants l'environnement. Le remplacement d'une partie du béton traditionnel par un matériau à base des déchets plastique aura des avantages économiques, sociaux et environnementaux importants. Allant dans ce sens, certains chercheurs ont utilisé les plastiques dans le béton et le mortier comme additifs et / ou substituts des matériaux granulaires tels que le sable et le gravier. Aussi, différents types de plastiques ont été utilisé dans le bitume comme additif pour réduire les coûts de construction et améliorer la durabilité, ainsi contribuer à donner de la valeur aux déchets. Cependant, jusqu'à présent, il existe peu d’informations techniques sur l'utilisation de déchets plastiques (HDPE et LDPE) fondus comme seuls liants pour développer de nouveaux types de matériaux de construction. En plus, plusieurs facteurs (les conditions de préparation, les éléments constitutifs, les applications finales, etc.) ont un impact sur les caractéristiques des matériaux de construction. Ainsi, l'objectif de cette recherche doctorale est de développer des nouveaux matériaux de construction (MPB et PWC) en utilisant les déchets plastiques fondus (HDPE et LDPE) comme seul liant, puis déterminer les propriétés caractéristiques de ces matériaux afin de trouver la formulation optimale conduisant à la meilleure résistance. En plus de l'élimination du coût du ciment, cette technologie permet aussi de faire des économies d'eau, bénéfique surtout pour les zones avec des difficultés d'accès à l’eau potable. Cela contribuera à la réduction des coûts de la construction en utilisant les produits innovants comme alternative au béton / mortier conventionnel. Un vaste programme expérimental, comprenant des tests à petite et grande échelle, a été développé afin d'atteindre les objectifs de cette étude de doctorat. La campagne expérimentale a comporté différentes étapes comprenant la sélection des matériaux, la détermination de la formulation optimale et les conditions appropriées pour la préparation des matériaux susmentionnés. Par la suite, pour une meilleure compréhension du comportement technique et des propriétés du produit final, divers tests ont été effectué sur les matériaux préparés à différents temps de durcissement. Ces tests ont été menés conformément aux normes ASTM pour évaluer les propriétés mécaniques (résistance à la compression et à la traction), la perméabilité et la densité des nouveaux matériaux. Les expériences ont été approfondies en analysant les produits au niveau microstructural (microscope optique, SEM, MIP et analyse thermique) pour avoir un aperçu des propriétés microstructurales des matériaux développés et essayer de comprendre les relations avec leur comportement mécanique. Les essais de compression ont permis de trouver la teneur en plastique optimale pour les matériaux (MPB et PWC) avec les meilleures valeurs de résistance. Les résistances moyennes à la compression à 28 jours pour diverses formulations étaient comprises entre 9 et 18 MPa. La résistance à la traction par fendage des nouveaux matériaux entre 1 et 28 jours se situait entre 1 et 5 MPa. La densité moyenne du béton et mortier écologique est proche de 2 g / cm3, ils peuvent donc être considérés comme des matériaux légers selon la classification RILEM. De plus, divers tests d'absorption (capillaire et par immersion) ont été réalisé sur différents échantillons de MPB et PWC, les résultats obtenus ont montré qu'il s'agit de matériaux poreux ayant un taux d'absorption plus faible que les matériaux traditionnels contenant du ciment. Plusieurs analyses microstructurales ont été réalisées sur différents échantillons des nouveaux produits (MPB et PWC) et les matériaux cimentaires traditionnels ont été utilisés pour renforcer notre compréhension. Enfin, l'analyse thermique a fourni des détails intéressants sur la décomposition thermique de ces nouveaux matériaux ; des changements significatifs avec une perte de masse considérable ont été observés seulement pour des températures supérieures à 300 ° C. Les résultats de ces essais permettent d'acquérir une bonne compréhension des propriétés techniques des nouveaux matériaux (MPB et PWC) ainsi que de déterminer les teneurs optimales en plastique conduisant aux meilleures performances en termes de résistance et de durabilité. Ainsi, les recherches menées dans cette étude de doctorat fournissent des informations techniques et des outils utiles sur le MPB et le PWC; et contribueront à installer des bases pour guider les applications optimales de ces nouveaux produits dans le domaine de la construction afin d'avoir des structures sûres, durables et rentables.
Keywords: Plastic waste; Pavers; Concrete; Cement; Recycling; Green materials; Building material; Sustainability; Curing conditions; Aggregate size; Construction materials; Ecological mortar